Integrasi Faktor Eksternal Dan Internal Dalam Pembentukan Kemampuan Akuntansi Siswa SMK Negeri Kabupaten Tangerang - Purnamasari, Atika; Sari, Mau Dhea; Sumaryo; Purwanti (JIBEMA: Jurnal Ilmu Bisnis, Ekonomi, Manajemen, dan Akuntansi, 2026)
This quantitative study aims to examine the influence of internship experience and learning quality on the accounting competency of state vocational high school students in Tangerang Regency, with learning motivation as a moderating variable. Data were collected from 200 12th-grade students through questionnaires using a purposive sampling technique. Data were then analyzed using multiple linear regression and Moderated Regression Analysis (MRA) using IBM SPSS Statistics. The results indicate that internship experience and learning quality significantly contribute to improving students' accounting skills. Similarly, independent learning motivation has been shown to enhance mastery of the material. However, the MRA test revealed that learning motivation did not act as a moderating variable. This means that students' internal motivation was unable to strengthen or weaken the effect of internships or mutual teaching on their technical competency achievement. Practically, these findings confirm that strengthening the accounting skills of vocational high school graduates is more effectively achieved through synchronizing relevant work experience programs and transforming interactive and applicable pedagogies. Focusing on these external elements is far more crucial than solely psychological interventions, given the procedural and exact nature of accounting competency. These results are expected to serve as a strategic reference for a more industry-oriented vocational development curriculum.